P634 Surveillance for disseminated gonococcal infections, active bacterial core surveillance (ABCs) – united states, 2015–2018. (14th July 2019) - Weston, Emily; Apostol, Mirasol; Moore, Ashley; Tunali, Amy; Farley, Monica; Sharpe, Samera; Mclean, Audrey Jeanine; Workowski, Kimberly; Torrone, Elizabeth; Weinstock, Hillard
Abstract : Background: Disseminated gonococcal infections (DGI) are uncommon; occurring in an estimated 0.5–3% of Neisseria gonorrhoeae (GC) cases. DGI surveillance is limited and case reports are often analyzed retrospectively or in case clusters. We describe the population-level burden of laboratory culture confirmed DGI using an established surveillance infrastructure, the Active Bacterial Core surveillance (ABCs) system of CDC's Emerging Infections Program. Methods: During 2017–2018, prospective surveillance was conducted among residents in three ABCs areas (3-counties in the Bay Area in California (CA), the 20-county Atlanta metropolitan area in Georgia [GA-MSA], and Georgia outside of the 20-county metropolitan area [GA-DPH]); retrospective surveillance was conducted during 2015–2016 in CA and GA-MSA. A DGI case was defined as isolation of GC from a normally sterile site; a case report form was completed for each case. Isolates collected during prospective surveillance underwent antimicrobial susceptibility testing (AST). Results: During 2015–2018, 53 DGI cases were identified (12 in CA, 6 in GA-DPH, and 41 in GA-MSA) for an overall rate of 0.11 cases per 100, 000 population (0.08 per 100, 000 in CA, 0.06 in GA-DPH, 0.16 in GA-MSA). DGI cases accounted for 0.06% of all reported cases of GC in the three surveillance areas. Most DGI cases were male (60%), aged 15–29 years (34%) or ≥ 45 years (34%), and were Black, non-Hispanic (58%). Clinical presentation was bacteremia (23%) or monoarticular septic arthritis (26%); 11% were immunocompromised. Of the 37 cases identified during 2017–2018, 18 viable isolates had AST completed. All were susceptible to Azithromycin, Ceftriaxone, and Cefixime; 6 (33%) were Penicillin and/or Ciprofloxacin resistant. Conclusion: DGI is an infrequent complication of GC. The ABCs infrastructure is a viable platform for DGI surveillance. As GC can quickly develop antimicrobial resistance, continued surveillance, including monitoring trends in antimicrobial susceptibility of DGI isolates and molecular epidemiology, could help inform DGI treatment recommendations. Disclosure: No significant relationships.